Effectiveness of cattle and buffalo expert system in knowledge management among the farmers - PONNUSAMY, K; SRIRAM, N; PRABHUKUMAR, S; VADIVEL, E; VENKATACHALAM, R; MOHAN, B (The Indian Journal of Animal Sciences, 2016)
Present investigation was conducted to assess the effectiveness of cattle and buffalo expert system which was developed under the network project on ‘Development of Expert System for Crop and Animal Enterprises’ with Central Institute for Women in Agriculture (CIWA) as the lead centre. The primary aim of the project was to develop an expert system on cattle and buffalo. The study was carried out to test the effectiveness of developed expert system in terms of knowledge gain and skill acquisition among the 140 farmers who were selected from two villages each from Panamarathupatti and Vazhapadi blocks of Salem district. The snow ball sampling method was used to identify four groups of farmers consisting of marginal and small size dairy farmers, medium size dairy farmers, big dairy farmers and women dairy farmers. The test verified pre and post exposure modules were developed for assessing the respondent’s knowledge gain and skill acquisition behaviour due to cattle and buffalo expert system in cattle. The study showed that medium and large size farmers gained relatively higher knowledge and skill due to their inclination towards undertaking dairy farming on commercial lines as compared to marginal farmers who took up the same at subsistence level in addition to other socio-economic characteristics. The study also brought out constraints and suggestions in improving the usage of expert system among all categories of farmers.